Photodynamic therapy directed to melanoma skin cancer by thermosensitive hydrogel containing Chlorophyll A - Araújo, Joabe Lima (2023)
Melanoma, a severe form of skin cancer intricately linked to genetic and environmental factors, is predicted to reach 100,000 new cases worldwide by 2040, underscoring the need for effective and safe treatment options. In this study, we assessed the efficacy of a photosensitizer called Chlorophyll A (Chl-A) incorporated into hydrogels (HGs) made of chitosan (CS) and poloxamer 407 (P407) for Photodynamic Therapy (PDT) against the murine melanoma cell line B16-F10. The HG was evaluated through various tests, including rheological studies, SEM, and ATR-FTIR, along with cell viability assays. The CS- and P407-based HGs effectively released Chl-A and possessed the necessary properties for topical application. The photodynamic activity of the HG containing Chl-A was evaluated in vitro, demonstrating high therapeutic potential, with an IC50 of 25.99 µM—an appealing result when compared to studies in the literature reporting an IC50 of 173.8 µM for cisplatin, used as a positive control drug. The developed formulation of CS and P407-based HG, serving as a thermosensitive system for topical applications, successfully controlled the release of Chl-A. In vitro cell studies associated with PDT exhibited potential against the melanoma cell line.